If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 2ln(x + 1) Multiply f * x fx = 2ln(x + 1) Reorder the terms: fx = 2ln(1 + x) fx = (1 * 2ln + x * 2ln) fx = (2ln + 2lnx) Solving fx = 2ln + 2lnx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 2lnx-1 + 2ln Simplifying f = 2lnx-1 + 2ln Reorder the terms: f = 2ln + 2lnx-1
| -5-6x+2x=-29 | | .4x-.5(2x+7)=-.7(X+4) | | 9+5x-3x=14+5 | | 7(x+2)=3x-3+4x | | 4x+3+6x+6=52 | | -5+6x-12y=24 | | 2x^2-13=10x | | -t=-2-10 | | inx+in(x-6)=in(2x) | | 8x-58=2*2+34 | | 8=8(1-6k) | | 1h=1 | | 6x+4x+6+4=38 | | -9+6w=5w | | a^2+1=29 | | 3(5y+2)-y=u+8 | | -92=4(-7x-2) | | 5x+55=9x-9 | | 2(3a+9)=20 | | 26p-4-11p=15p+6 | | 8x-4=4x+44 | | -6(4x+7)=78 | | -7p-39=5(-5p+3) | | -8(2x-2)=128 | | -14+4x-2x=30 | | P=A-ArT | | X^2+4y^2+6x+16y=11 | | 3x^26y-24=0 | | 10(9-x)= | | 35-(2c+3)=2(c-6)+c | | -7p-39=5(-5p+30) | | 3y+6x=360 |